Cooperative Learning in Swedish Classrooms: Engagement and Relationships as a Focus for Culturally Diverse Students - Kate Ferguson-Patrick (MDPI AG, 2020)
The ongoing refugee crisis makes intercultural competence and culturally responsive education crucial issues in schools. At the same time, increased migration poses new challenges for social cohesion in countries around the world. How schools and classrooms can be fair and inclusive in terms of experiences and outcomes for migrant and refugee students is therefore a key question. This paper will explore the increase in migration of newly arrived students in Sweden, and how teachers in this country are catering for diverse students through cooperative learning. I explore cooperative learning as an inclusive and culturally responsive pedagogy that can be effectively used in schools to support all students and especially 'refugee' or newly arrived students. Using theory from cooperative learning and Stembridge (2020) as a theoretical framework, I particularly focus on analysis using two of Stembridge's themes of Culturally Responsive Education: Engagement and Relationships to analyze Swedish primary school classroom observations and teacher interviews and find commonalities between these two themes and the key ideas in cooperative learning. This research is built on the premise that there is more need in education research for up to date observations into the classroom factors that support or hinder learning and the way that within-class groupings can support diversity and inclusivity. Cooperative learning allows participants to develop a commitment to fairness, social responsibility and a concern for others and this particularly caters for our diverse student populations.